La lectura de Pacem in terris a propósito de las minorías étnicas - Compte Grau, María Teresa (Estudios eclesiásticos, 2005)
Pacem in Terris was published in a world divided into two blocks, at a time characterised by the globalisation of social issues and by processes of national emancipation of the former colonies. Its main aim was to achieve a new order of peaceful coexistence. Its doctrinal core put God as the only foundation of a firm moral order and the human being as the subject of rights and duties which arise from their own nature. Following from this doctrinal foundation, the Encyclical develops models of how human socialise, the relations of individuals to their political communities, and between international communities and the geo-political order. This article studies the ordering of international relations from the point of view of ethnic minorities and their rights. According to the Church’s Social Doctrine, the aspirations of free and deliberately organised political coexistence is not a result of will, but an answer to human nature.